Management of Prolonged Pulmonary Air Leaks With Endobronchial Valve Placement - Bakhos, Charles (JSLS, 2016)
BACKGROUND: Prolonged pulmonary air leaks (PALs) are associated with increased morbidity and extended hospital stay. We sought to investigate the role of bronchoscopic placement of 1-way valves in treating this condition. METHODS: We queried a prospectively maintained database of patients with PAL lasting more than 7 days at a tertiary medical center. Main outcome measures included duration of chest tube placement and hospital stay before and after valve deployment. RESULTS: Sixteen patients were eligible to be enrolled from September 2012 through December 2014. One patient refused to give consent, and in 4 patients, the source of air leak could not be identified with bronchoscopic balloon occlusion. Eleven patients (9 men; mean age, 65 ± 15 years) underwent bronchoscopic valve deployment. Eight patients had postoperative PAL and 3 had a secondary spontaneous pneumothorax. The mean duration of air leak before valve deployment was 16 ± 12 days, and the mean number of implanted valves was 1.9 (median, 2). Mean duration of hospital stay before and after valve deployment was 18 and 9 days, respectively (P = .03). Patients who had more than a 50% decrease in air leak on digital monitoring had the thoracostomy tube removed within 3–6 days. There were no procedural complications related to deployment or removal of the valves. CONCLUSIONS: Bronchoscopic placement of 1-way valves is a safe procedure that could help manage patients with prolonged PAL. A prospective randomized trial with cost-efficiency analysis is necessary to better define the role of this bronchoscopic intervention and demonstrate its effect on air leak duration.